Retinopathy of prematurity: incidence and risk factors: a hospital based study from Shimla, Himachal Pradesh, India - Kumar, Nitin; Kaushik, Shayam L.; Grover, Neelam; Sharma, Ram L. (International Journal of Research in Medical Sciences, 2016)
Background: The blindness due to retinopathy of prematurity (ROP) is avoidable, if it is detected in time by screening. With increasing survival of preterm and low birth weight newborns in neonatal units, who are on prolonged oxygen therapy and mechanical ventilation; ROP is bound to affect these babies. This study was planned to investigate the incidence and the risk factors of ROP in a tertiary care institute in Himalayan region of north India. Methods: This was a hospital based prospective study, conducted at neonatal intensive care units at IGMC, Shimla, from June 2011 to July 2012. 64 premature and low birth weight neonates born or admitted for neonatal intensive care unit (NICU) were screened for ROP using indirect ophthalmoscope. Cases found positive for ROP were closely followed up and managed as per international guidelines. Results: Out of 64 neonates, 14 were lost to follow up and 50 babies were enrolled in the study. Out of them 21 were males and 29 were females. Among them 3 male and 5 female newborns developed ROP. Mean gestational age of babies with ROP was 30.63 weeks. ROP was significantly associated with oxygen administration (p=0.027), RDS (p=0.003), septicaemia (p=0.028) and exchange transfusion (p=0.003). Apneic spells, surfactant administration, hyperbilirubinemia, phototherapy, blood transfusion and maternal factors were not associated with increased risk of ROP. Conclusions: For premature infants with birth weight less than 1200 grams, who has received prolonged oxygen therapy, associated respiratory distress and had received exchange transfusion the screening of ROP should be done at most appropriate time that is 32 - 40 weeks of gestational age. Timely referral of detected ROP cases for early treatment prevents blindness. There is a need for the obstetricians, neonatologist and ophthalmologist to work in close co-operation to prevent blindness due to ROP.